2014
DOI: 10.2138/am.2014.4585
|View full text |Cite
|
Sign up to set email alerts
|

Pressure-induced phase transitions in coesite

Abstract: High-pressure behavior of coesite was studied on single crystals using diamond-anvil cells with neon as the pressure-transmitting medium by means of in situ Raman spectroscopy up to pressures of ~51 GPa. The experimental observations were complemented with theoretical computations of the Raman spectra under similar pressure conditions. We find that coesite undergoes two phase transitions and does not become amorphous at least up to ~51 GPa. The first phase transition (coesite I to coesite II) is reversible and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
26
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 45 publications
5
26
0
Order By: Relevance
“…The pressure dependence of the Raman band can be therefore fitted by a linear function ν(P) = 3.580P + 518.4 (R 2 = 0.9855). The regression line obtained from previous work (Cernok et al, 2014) coincides with our observation. It is already known that colloidal silica, often called silica gel, is readily transformed to coesite at 5 GPa and 100°C for 1 h (Arasuna et al, 2014).…”
Section: Structural and Morphological Changes Of Biogenic Hydrous Amosupporting
confidence: 92%
See 2 more Smart Citations
“…The pressure dependence of the Raman band can be therefore fitted by a linear function ν(P) = 3.580P + 518.4 (R 2 = 0.9855). The regression line obtained from previous work (Cernok et al, 2014) coincides with our observation. It is already known that colloidal silica, often called silica gel, is readily transformed to coesite at 5 GPa and 100°C for 1 h (Arasuna et al, 2014).…”
Section: Structural and Morphological Changes Of Biogenic Hydrous Amosupporting
confidence: 92%
“…A structure with four-membered SiO 4 rings such as found in moganite, coesite, and feldspars, should possess symmetric Si-O-Si stretching and bending modes above 500 cm −1 (Kingma and Hemley, 1994). At ambient conditions, the characteristic Raman band of coesite can be observed at around 520 cm −1 (Kingma and Hemley, 1994;Cernok et al, 2014). The Raman peak at 520 cm −1 increases approximately linearly with compression up to 10 GPa (Cernok et al, 2014).…”
Section: Structural and Morphological Changes Of Biogenic Hydrous Amomentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier spectroscopic studies observed structural changes in coesite near ∼ 23 GPa [11] , and one more near ∼ 34 GPa, with the latter polymorph remaining crystalline at least up to ∼ 51 GPa [10] . Reconstructive transitions to the stable high-pressure polymorphs consisting of SiO 6 octahedra (e.g., stishovite, CaCl 2 -structured silica, or seifertite) are often hindered due to high kinetic barriers associated with the relatively strong Si-O bonding within the tetrahedra (e.g., [12] ).…”
Section: Introductionmentioning
confidence: 89%
“…Our recent study [10] has shown that coesite, similarly to quartz and cristobalite, can be compressed under (quasi)-hydrostatic conditions to very high pressures and at ambient temperatures without undergoing amorphization. Earlier spectroscopic studies observed structural changes in coesite near ∼ 23 GPa [11] , and one more near ∼ 34 GPa, with the latter polymorph remaining crystalline at least up to ∼ 51 GPa [10] .…”
Section: Introductionmentioning
confidence: 97%